Photocatalytic and Reusability Studies of Novel ZnSe/Graphene Nanocomposites Synthesized via One Pot Hydrothermal Techniques - Ullah, Kefayat; Zhu, Lei; Ye, Shu; Jo, Sun-Bok; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
Novel photocatalyst ZnSe/graphene nanocomposites were synthesized by facile hydrothermal techniques. The “as-prepared” nanocomposites are further characterized by various techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM) with an energy dispersive X-ray (EDX) analysis, transmission electron microscopy (TEM), UV-visible absorbance spectra analysis and Raman spectroscopic analysis. The photocatalytic activities of the composites were investigated by the degradation of Methylene orange and Rhodamine-B as a standard dyes. The photodegradation rates of organic dyes by the nanocomposites are found to be markedly high. Reused ZnSe/graphene showed very minute change in degradation efficiency which indicates excellent stability of our photocatalyst materials.